"O paraíso termina quando o trabalho começa" : cotidiano operário e poder disciplinador na Fábrica Têxtil Confiança (Sergipe, 1943-1957) - Santos, Wagner Emmanoel Menezes (2014)
The emergence of factories marked the society, transforming the habits and relations between individuals, new technologies emerged, and even the notion of time gained another sense. The man had to sell their labor to the industrial capitalist part of the wage process, and so he was subjected to daily life within the industry through long working hours, strict schedules, etc. Many workers faced these working conditions in Brazil, especially in the early years of the republican period. In Sergipe, textile industries contributed to the development of the state bringing social, political and cultural changes. To understand the growth of the textile industry and the workers daily lives, this research examined the lives of workers (food, housing, clothing, leisure, internal conflicts, etc.) within and outside the Confiança factory, founded in 1907, in Aracaju, and that had Joaquim Sabino Ribeiro as chief director. The time frame includes 1943, year of the emergence of CLT (Consolidation of Labor Laws) which aimed to further regulate the labor laws and the conflicting relationship between employer and employee, until 1957, when the crisis happens in the national textile industry which had the dismissal of several workers, including affecting sergipanos workers. The sources used were Poliantéa magazine, periodicals Fôlha Popular and Gazeta Socialista, works of memoir Mário Cabral and Melins Murillo, the literature Amando Fontes and especially, labor claims brought by workers against Confiança factory. The theoretical contribution of this research is based on the concept of discipline, proposed by Michel Foucault, in order to understand how was the process of disciplining the daily lives of workers of Confiança factory.